2014
DOI: 10.7785/tcrt.2012.500425
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Study of Cobalt Based Stereotactic Body Radiation Therapy for Patients with Inoperable Stage III Non-small Cell Lung Cancer

Abstract: Aim of this paper is to retrospectively evaluate the efficacy and toxicity of specialized Body Cobalt based system (BCBS) treatment in the senior patients group (.65 years) with Stage III non-small cell lung carcinoma (NSCLC). A total of 49 patients (41 males and 8 females) with Stage III NSCLC according to UICC TNM classification (6(th) edition) were treated using OUR-QGD™ BCBS which was designed and manufactured in China. Post treatment evaluation with follow-up information was collected from April 2001 to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The physical characteristics of RGS including radiation absorbed dose rates and profiles measured are well comparable to those measured for the commonly used Leksell Model U Gamma Knife ® unit (Goetsch et al 1999). The efficacy of gamma ray systems has been shown for both early stage and inoperable locally advanced lung cancer and in treating metastatic liver lesions (Kishan et al 2015, Wang et al 2015, Merna et al 2016. The preliminary results, done with Monte Carlo simulations, showed great potential for a novel-design RGS when compared to the well-established CyberKnife system (Eldib et al 2016a).…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…The physical characteristics of RGS including radiation absorbed dose rates and profiles measured are well comparable to those measured for the commonly used Leksell Model U Gamma Knife ® unit (Goetsch et al 1999). The efficacy of gamma ray systems has been shown for both early stage and inoperable locally advanced lung cancer and in treating metastatic liver lesions (Kishan et al 2015, Wang et al 2015, Merna et al 2016. The preliminary results, done with Monte Carlo simulations, showed great potential for a novel-design RGS when compared to the well-established CyberKnife system (Eldib et al 2016a).…”
Section: Introductionsupporting
confidence: 54%
“…The main design is to focus multiple Cobalt-60 sources on target by cone shaped style rotation of the system. These sources rotate along the same axis so that the lesion at a constant focal point receives continued irradiation, whereas, surrounding normal tissue has instantaneous low dose irradiation during delivery of treatment (Wang et al 2015). Although in our results the estimated treatment time from the RGS system was comparatively less than that from CyberKnife, it could be argued that one of the drawbacks of using Cobalt-60 is the dose rate change due to the course of its useful lifespan.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…22 Through changing the fractionated radiotherapy dose of 2.5-6 Gy with concurrent chemoradiotherapy for locally advanced NSCLC, the CR, PR, 1, 2, 3 years OS rates, and MST were 26.5%, 42.9%, 63.3%, 40.8%, 20.4%, and 22 months, respectively. 23 A fraction dose of 3 Gy and total dose of 65-68 Gy were given after initially 50 Gy/20 fractions, the 3-years OS and progression-free survival (PFS) rates were 32.1% and 29.8%, respectively, and the 1-, 2-, and 3-years LRPFS rates were 69.6%, 60.9%, and 60.9%, respectively. 24 Based on the characteristics of IMRT, the dose of the PTV was kept at 60 Gy and the dose of GTV was 72-78 Gy synchronously, the result showed that MST was 25.3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Through changing the fractionated radiotherapy dose of 2.5-6Gy with concurrent chemoradiotherapy for locally advanced NSCLC ,the CR ,PR,1, 2, 3 years OS rates and mean suivival time(MST) were 26.5%, 42.9%,63.3%, 40.8%, 20.4% and 22 months, respectively [20] . A fraction dose of 3 Gy and total dose of 65-68Gy were given after initially 50 Gy/20 fractions the 3-years OS and PFS rates were 32.1% and 29.8% respectively and the 1 -, 2-and 3-years LRPFS rates were 69.6%, 60.9% and 60.9%, respectively [21] .…”
Section: Discussionmentioning
confidence: 99%